Novel Compound Heterozygous Pathogenic Variants in SUOX Cause Isolated Sulfite Oxidase Deficiency in a Chinese Han Family - Zhao, Jiangang; An, Yao; Jiang, Haoxiang; Wu, Haibin; Che, Fengyu; Yang, Ying (Frontiers in Genetics, 2021)
Aim To explore the clinical imaging and laboratory and genetic characteristics of a newborn boy with isolated sulfite oxidase deficiency (ISOD) in a Chinese mainland cohort. Methods Homocysteine and uric acid in plasma and cysteine and total homocysteine in the blood spot were assessed in a Chinese newborn patient with progressive encephalopathy, tonic seizures, abnormal muscle tone, and feeding difficulties. Whole exome sequencing and Sanger sequencing facilitated an accurate diagnosis. The pathogenicity predictions and conservation analysis of the identified mutations were conducted by bioinformatics tools. Results Low cysteine and total homocysteine were detected in the blood spot, while homocysteine and uric acid levels were normal in the plasma. S-sulfocysteine was abnormally elevated in urine, while cystine was normal. A follow-up examination revealed several progressive neuropathological findings. Also, intermittent convulsions and axial dystonia were observed. However, the coordination of sucking and swallowing was slightly improved. A novel paternal nonsense variant c.475G>T (p.Glu159*) and a maternal missense variant c.1201A>G (p.Lys401Glu) in SUOX were identified in this case by co-segregation verification. Conclusion This is the second report of early-onset ISOD case in a non-consanguineous Chinese mainland family. Combined with the clinical characteristics and biochemical indexes, we speculated that these two novel pathogenic variants of the SUOX gene underlie the cause of the disease in this patient. Next-generation sequencing (NGS) and Sanger sequencing provided reliable basis for clinical and prenatal diagnoses of this family. It also enriched the mutation spectrum of the SUOX gene.